STRATEGI PENGEMBANGAN AGROINDUSTRI KERUPUK TERASI (Studi Kasus Di Desa Plosobuden, Deket, Lamongan) - Khoiriyah, Nur R.; Ariyani, Aminah H.M.; Fauziyah, Elys (9-772301-994005, 2013)
This study aims to identify the internal and external environment of agro-shrimp crackers and formulate strategies to develop these agro-industry inÂ  Plosobuden Village, Deket District, Lamongan Regency.The basic method used in this research is descriptive qualitative method and carried out with a case study. The analysis used was the marketing environment analysis, the SWOT analysis to identify internal and external factors for the strengths, weaknesses, opportunities and threats, the IFE and EFE Matrix and the SWOT matrix to formulate an alternative strategy in business development. Based on research result shows that the main internal strengths which is owned by agro-shrimp crackers entrepreneur is selling at an affordable price. While its main weaknesses is the lack of promotion. The main opportunities in the agro-shrimp cracker development is still has an extensive market share. While the main threats is unfavorable weather in the shrimp cracker business. Alternative strategies can be applied in developing agro-industry is raising the shrimp crackers production to take the opportunities of technological advancement for food security standards, promoting to attract potential customers in anticipating the new competitors to improve the image of the product, making business licenses and increasing the products diversification through products and services policy dealing with new competitors.